Empowerment of the Disaster Risk Reduction Forum (FPRB) through communication monitoring tools for cold lava floods in Sumber Village, Magelang Regency - Adhianty Nurjanah; Iswanto Iswanto; Nano Prawoto (Community Empowerment, 2022)
When the Merapi eruption happened in 2010, members of the Disaster Risk Reduction Forum (FPRB) as well as disaster communicators in Sumber Village, Magelang Regency, still had limitations in using communication and information technology to carry out disaster mitigation. As a result, community-based disaster mitigation communication tools and training are required. This service will be implemented by providing training and assistance to participants on how to use cold lava communication monitoring tools. According to the findings, 85 percent of the participants improved their knowledge and skills in the area of community-based disaster communication. As a result of this service, the Sumber Village FPRB community now has a monitoring tool that can also be used as a disaster communication tool.